The Role of Profitability as an Intervening Variable in the Influence of Capital Intensity Ratio and Leverage on Corporate Tax Management - Yuni, Sri; Christian, Ferry; Okta, Okta (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2025)
Purpose: The purpose of this study is to determine the role of profitability as a mediating variable in the influence between capital intensity ratio and leverage on tax management. Methodology: The method used in this study is quantitative research. Hypothesis testing in this study uses path analysis with SPSS 25. Findings: The findings of this study indicate that capital intensity ratio and leverage have a significant effect on profitability. While capital intensity ratio, leverage and profitability have a significant effect on tax management. However, the profitability variable does not mediate the relationship between capital intensity ratio and leverage on tax management. Implication: This study can be useful for companies in making decisions related to tax management. Originality: This study offers an approach for companies in understanding how capital structure, capital intensity, and profitability interact in the context of tax management.